Relationship between religious background, intergroup contact and acceptance of LGBT in Malaysia - Ting, Su Hie; Hsin-Nie, Ling (Academia Industry Networks, 2022)
Attitudes towards homosexuality have been found to vary with religious background and contact with LGBT individuals. Intergroup contact may result in more favourable attitudes towards homosexuality and research has suggested that the people who are more open to gender non-conformity may be young, female and non-religiously affiliated. However, in the Malaysian context, the degree of acceptance towards LGBT in relation to religious background and intergroup contact is not well understood. The study examined the relationship between religious background, intergroup contact and acceptance of LGBT in Malaysia. The specific objectives of the study are to determine: (1) the level of intergroup contact with LGBT individuals for respondents from different religious backgrounds; (2) the degree of acceptance towards LGBT individuals for respondents from different religious backgrounds; and (3) relationship between intergroup contact and acceptance towards LGBT individuals. The questionnaire data were from 364 heterosexual Malaysian respondents from various age, ethnic, and religious backgrounds. The results showed that about half of respondents have direct contact with LGBT individuals as in having close friends who are LGBT or knowing a LGBT couple but very few have attended a marriage ceremony for LGBT couples, are in a romantic relationship with LGBT individuals or are LGBT themselves. A majority of the respondents know the challenges of LGBT individuals through reading about them but few have taken active steps to express public support for LGBT. The respondents can accept it if they found out their friends, neighbours, colleagues, educators and close relatives are LGBT but are not as tolerant if their child or religious leader is International Journal of Social Science Research eISSN: 2710-6276 | Vol. 4, No. 1, 339-354, 2022 http://myjms.mohe.gov.my/index.php/ijssr340 Copyright © 2022 ACADEMIA INDUSTRY NETWORKS. All rights reserved. 1. Introduction Lesbian, Gay, Bisexual and Transgender (LGBT) individuals often hide their sexual orientation because of the prevalence of heteronormative behaviour in the society (Mkhize et al., 2020). On social media, for example, there are hate speech and violent comments which cause anxiety, depression and stress to LGBT individuals (Hubbard, 2020). Over the years, acceptance towards LGBT individuals has increased in many developed countries (Ayoub & Garretson, 2017) including Australia and Canada. In most Western societies, people are more supportive towards LGBT rights (Van Lisdonk, 2018). In Asia, Taiwan is the first country to legalise same-sex marriage on 24 May 2019. However, sexual orientation prejudice still exists where people hold the beliefs that “homosexuality is wrong” (Morrison & Morrison, 2003). For instance, some people feel disgusted to see same-sex couples acting intimately in public (Kiebel et al., 2016). In countries where Islam is the main religion, like Malaysia, the LGBT lifestyle is frowned upon. LGBT practice is against Islamic principles and teachings (Muhammed & Amuda, 2018). In Malaysia, the state-level Sharia (Islamic) laws prohibit cross-dressing, and transgender people “face arbitrary arrest, physical and sexual assault, imprisonment, discriminatory denial of health care and employment, and other abuses” (Human Rights Watch, 2015). According to Lee (2012), the basic human rights of LGBT individuals in Malaysia have been frequently violated. He cited the Amnesty International (2007) report that shows that LGBT individuals have been assaulted by vigilantes and those in official positions such as the police. Jerome (2013) found that queer Malay Muslims themselves often have the conflict between their religious beliefs and sexualities due to the heteronormative Malay Muslim community. Not surprisingly, LGBT individuals in Malaysia choose to hide their LGBT identities to avoid discrimination and prejudice. Religious belief is one of the main factors that causes negative attitudes towards LGBT. Up to 2018, the Malaysian Islamic Development Department (JAKIM) has reported that the number of gay men has increased from 173,000 to 310,000 in five years. The increase of LGBT individuals would lead to greater contact of heterosexuals with LGBT individuals in daily life. Intergroup contact can act as a mechanism to promote the acceptance towards LGBT and reduce negative stigma towards them (Hoffarth & Hodson, 2020). Researchers have found that intergroup contact influences acceptance towards LGBT individuals. In Western settings, intergroup contact can reduce discrimination and prejudice towards LGBT (Collier et al., 2013; Fingerhut, 2011; Hoffarth & Hodson, 2018). However, little is known about intergroup contact with LGBT individuals in Malaysia. Earnshaw et al. (2016) reported that medical and dental students who had interpersonal contact with men who have sex with men (MSM) are more likely to be less prejudiced and less discriminating towards MSM. In addition, Ahmad et al.’s (2021) findings based on interviews with 12 participants LGBT. The acceptance of LGBT individuals is significantly correlated with religious background and extent of intergroup contact with LGBT individuals.